Five Years Data of Clinical and Histopathological Characteristics of Skin Adnexal Tumors in Dr. Hasan Sadikin General Hospital Bandung - Trisaputra, Jessica Oktavianus; Usman, Hermin Aminah; Hindritiani, Reti (Althea Medical Journal, 2016)
Background: Skin adnexal tumors arise from skin adnexal differentiation. Very limited number of study has been performed on their clinical and histopathological characteristics in Dr. Hasan Sadikin General Hospital. The objectives of this study was to identify the clinical and histopathological characteristic of skin adnexal tumors during the period of 2009 to 2013.Methods: AA descriptive study performed on 79 medical records of patients with skin adnexal tumors at the Department of Anatomic Pathology in Dr. Hasan Sadikin General Hospital Bandung from 2009 to 2013. Data were collected during the period of September to October 2014. The inclusion criteria were medical records containing information on skin adnexal tumors confirmed by histopathological examination results, patient characteristics (age and gender), and the tumor characteristics (size, location, malignancy, type, and histopathological origin). Collected data were processed using computer and presented in tables.Results: This study showed that tumors occured during productive age with male to female ratio was 1.2:1. Most skin adnexal tumors were â¤5 cm in size and were distributed in the head-neck region. Most of the tumors were benign and arised from hair follicle differentiation with pilomatricoma type while the malignant tumors commonly arised from sebaceous gland differentiation with sebaceous carcinoma type.Conclusions: Most skin adnexal tumors occur in productive age with no gender prediclation. They are small in size and are distributed in the cephalic region. Most are benign tumors arising from hair follicle differentiation with some malignant tumors arising from sebaceous gland differentiation. [AMJ.2016;3(4):514â9]Â DOI:Â 10.15850/amj.v3n4.933